Slide operation method for a touch screen – the concept of connecting audio component. (2nd April 2016) - Lee, Kuo-Wei
Abstract : Smartphone operation currently follows the graphical user interface operation framework. Each of a product's functions is executed by clicking or sliding the function icon. The graphical user interface is simple and easy to learn, and the vision-oriented operation was applicable to personal computers in the past. However, this design may not be suitable for multi-operational smartphones, for example, those that use in a dynamic operating environment. This study designs a method for using sliding operation on a touch screen in which a simple sliding operation is linked to multiple audio signals. With this design, the user can quickly activate the product's functions using a sliding operation combined with audio signals without relying on vision. Thus, the diverse operational needs of smartphone users can be satisfied. With the foregoing discussion, the present study hopes to provide an improved and practical user interface for Taiwan's mobile phone industry.